1978
DOI: 10.1002/clc.4960010202
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial imaging with extractable cations and inert tracers: The effects of flow and metabolism

Abstract: The physical and biological properties of 201thallium (Tl) have been investigated and are discussed in this review. A new technique using the ultra-short lived 81mkrypton (81mKr) as a continuous infusion into the aortic root in dogs and man is described. This provides a dynamic assessment of changes in regional myocardial perfusion. Experiments using 201Tl and 81mKr in dogs have shown that regional decreases in myocardial perfusion alone cannot be detected in images of the heart using 201Tl. The effects of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Time-activity graphs with tables of the counts per minute in each area of interest were recorded with the serial images of regional myocardial perfusion from each study. [5][6][7] The nature, intention and potential dangers of the procedure were explained to each patient before each study. Subjects gave signed consent as required by the Hospital Ethics Committee, and Isotope Panel clearance was obtained before the studies.…”
Section: Krypton-81m Scintigraphymentioning
confidence: 99%
“…Time-activity graphs with tables of the counts per minute in each area of interest were recorded with the serial images of regional myocardial perfusion from each study. [5][6][7] The nature, intention and potential dangers of the procedure were explained to each patient before each study. Subjects gave signed consent as required by the Hospital Ethics Committee, and Isotope Panel clearance was obtained before the studies.…”
Section: Krypton-81m Scintigraphymentioning
confidence: 99%
“…Previous work has shown that when the catheter seated in the aortic sinus is sta ble a constant infusion of 81 mKr can be used to continuously image changes in regional myocardial perfusion (Selwyn et al .. 1978a). Further, provided the alterations in heart rate are within those seen in this study the concentration of indicator delivered to the coronary circulation is not altered (Selwyn et al .• 1978a,c).…”
Section: Discussionmentioning
confidence: 63%
“…Time-activity graphs were calculated by a Deltron-Nova 1220 digital computer and corrected for the decay of rubidium-81 (half-life 4.56 hours). [8][9][10][11][12] A Wilcoxon test for paired differences was used to test changes in end-diastolic pressure, blood pressure and heart rate. An analysis of variance was used to examine the significance of changes in the regional myocardial activity of krypton-81m.…”
Section: Methodsmentioning
confidence: 99%